Japanese education : - Passin, Herbert (Teachers College Press, 1970)
The purpose of this annotated bibliography is to provide researchers, analysts, teachers, and advanced students, interested in various aspects of Soviet education, with a body of reference materials covering the large number of relevant articles and monographs which have been published since the late 1950's. The bibliography includes 281 titles with a 36-title supplement, arranged alphabetically by authors within 78 subject categories; where necessary, cross-referencing is used. Although American authors are the primary sources, items by foreign authors, whose articles are written in English or have been translated into English, are also included. A number of the English translations of articles and monographs by Soviet authors are the work of the Joint Publications Research Service, Office of Technical Services, U. S. Deaprtment of Commerce. A wide range of views is expressed in the annotated items, and their inclusion does not constitute endorsement by the Office of Education of any one point of view. The Soviet articles provide the researcher and serious scholar certain information not found in the other sources, as well as insight into the Soviet concept of the educational system. The purpose of this annotated bibliography is to provide researchers, analysts, teachers, and advanced students, interested in various aspects of Soviet education, with a body of reference materials covering the large number of relevant articles and monographs which have been published since the late 1950's. The bibliography includes 281 titles with a 36-title supplement, arranged alphabetically by authors within 78 subject categories; where necessary, cross-referencing is used. Although American authors are the primary sources, items by foreign authors, whose articles are written in English or have been translated into English, are also included. A number of the English translations of articles and monographs by Soviet authors are the work of the Joint Publications Research Service, Office of Technical Services, U. S. Deaprtment of Commerce. A wide range of views is expressed in the annotated items, and their inclusion does not constitute endorsement by the Office of Education of any one point of view. The Soviet articles provide the researcher and serious scholar certain information not found in the other sources, as well as insight into the Soviet concept of the educational system.